REPRESENTASI IBU DALAM SASTRA ANAK DI INDONESIA (Studi Kasus Terhadap Sastra Anak Karya Anak Periode 2000-an) - Hayati, Yenni (Humanus, 2014)
Child-created children’s literature that grown in Indonesia in 2000s, particular-ly those about family, tends to describe women as mothers. This is because the young writers still live with their mothers that the nurturing habits of the mother are reflected in their writing. The mothers in the child-created children’s literature are described as beautiful, smart, self-reliant, and independent from their husbands (the fathers) in making decisions about the children. This pleasures the children and helps them in self-improvement. The mothers in the literature are also described as the women who are active in domestic as well as public life.Key words: women’s representation, child-created children’s literature, mother